Construction of neophallus in male pseudohermaphroditism - Kruk-Jeromin, J (Acta chirurgiae plasticae, 1996)
Eight patients with male pseudohermaphroditism were treated between the years 1988-1994. They showed various physical-sexual anomalies. In 4 patients the existing penis was lengthened, the urethra was created and the split scrotum was fused. In the 4 remaining patients a new penis was created from lateral groin or abdominal tubed or skin-gracilis flaps, and made rigid by means of a silicon implant. The scrotum was reconstructed. The results were satisfying. On the basis of our own experience it may be said that the reconstruction of genitals must be planned individually, depending on the abnormalities in the physical-sexual development and the psycho-sexual orientation of the patient.
Keywords: estetika; Scrotum; plastická chirurgie; Humans; Esthetics; transplantace kůže; Psychosexual Development; dospělí; skrotum; Penis; lidé; uretra; mladiství; penis; penilní protézy; Surgical Flaps; Adult; Urethra; kosterní svaly; Penile Prosthesis; poruchy sexuálního vývoje; psychosexuální vývoj; Male; Adolescent; Muscle, Skeletal; chirurgické laloky; Surgery, Plastic; Silicon; Disorders of Sex Development; mužské pohlaví; Skin Transplantation; křemík